PENGARUH RISIKO KREDIT DAN UKURAN PERUSAHAAN TERHADAP NET INTEREST MARGIN (NIM) DI SEKTOR PERBANKAN - Abubakar Arif (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study was to examine the effect of credit risk and company size on Net Interest Margin (NIM) in the banking sector. The samples used are banks that fall into the category of BUKU 1 to BUKU 4 banks, totaling 99 banks with observation periods from 2010 to 2014. The sampling technique uses purposive sampling. The analysis method used is multiple regression with data panel. The chosen model is Fixed Effect Model (FEM). The results showed that the size of the company had a negative and significant influence on net interest margins while credit risk had no significant effect on the net interest margin.